2002
DOI: 10.1109/59.982189
|View full text |Cite
|
Sign up to set email alerts
|

Incremental transmission loss allocation under pool dispatch

Abstract: Incremental transmission loss analysis has been used for decades, but recent interest in its application to loss allocation calls for new in-depth results. This paper demonstrates that, for incremental methods to be applied correctly in loss allocation, it is first necessary to specify the load distribution and loss supply strategies. Incremental loss allocation among bus power injections is shown to be arbitrary and, therefore, open to challenge as discriminatory. Loss allocation is possible among incremental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(44 citation statements)
references
References 13 publications
0
44
0
Order By: Relevance
“…In the case of a bus with a net generation, the allocated losses are divided pro-rata between the generation and the demand of that bus. Table 9 shows the comparison of the Shapley Value procedure (SV) with four different loss allocation procedures: Zbus [3], incremental transmission losses (ITL) [13], proportional sharing (PS) [2] and pro-rata (PR) [20]. For this example, it can be observed that the results from the SV method are almost equal to the ones from the ITL procedure, since both of them involve successive increments in the value of losses.…”
Section: Coalitionmentioning
confidence: 72%
See 1 more Smart Citation
“…In the case of a bus with a net generation, the allocated losses are divided pro-rata between the generation and the demand of that bus. Table 9 shows the comparison of the Shapley Value procedure (SV) with four different loss allocation procedures: Zbus [3], incremental transmission losses (ITL) [13], proportional sharing (PS) [2] and pro-rata (PR) [20]. For this example, it can be observed that the results from the SV method are almost equal to the ones from the ITL procedure, since both of them involve successive increments in the value of losses.…”
Section: Coalitionmentioning
confidence: 72%
“…Several methods have been proposed in the last few years, among them: methods based on network matrices [3], methods based on proportional sharing [1,2], methods based on incremental transmission losses [13], methods based on the pro-rata technique [20] and methods based on bilateral contracts [10,12]. A comparative revision of some of these methods is presented in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Just as there is no a unique method for allocating real power losses [20][21][22][23], there are also alternative methods for allocating reactive power losses. Two methods are proposed here, namely, the proportional allocation method and the quadratic allocation method.…”
Section: Tracing Power Flow and Allocating Reactive Lossesmentioning
confidence: 99%
“…Total real energy losses ∆W to be allocated among network users is evaluated by EV penetration level using Equation (9) and results are depicted in Figure 4. This figure also shows the resultant load and loss factor.…”
Section: Scenario 1: Slow Charging At Off-peak Load Conditionsmentioning
confidence: 99%
“…In general, the majority of the loss allocation procedures discussed in the literature are based upon positive-sequence power flow models with balanced power injections where all loads are modeled using standard constant real and reactive power (PQ) models [7][8][9]. In this case, load demands are not affected by voltage fluctuations (constant power load models).…”
mentioning
confidence: 99%